2019
DOI: 10.1016/j.jiac.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Salmonella enterica serovar Agona strains and their similarities to strains derived from a clone caused a serovar shift in broilers

Abstract: Salmonella enterica serovar Agona strains isolated from human cases were compared to strains that were derived from a clone caused a serovar shift in broilers. Pulsed field gel electrophoresis (PFGE) analysis with XbaI or BlnI digestion showed that three of seven strains from human case strains and most of the 81 strains from broilers were clustered in single complex in a minimum spanning tree (MST) reconstructed from the PFGE data. All the strains from human cases and 22 randomly selected strains from broiler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Here, all isolates from two each of sewage and human samples, belonging to this serotype, were concurrently identified in June 2019 (Table 3), and their PFGE patterns were indistinguishable from each other (Figure 1c). Moreover, serovar Agona strain 14-8, which was isolated from human and clustered with the isolates from broilers in the Yamanashi Prefecture using whole-genome sequencing [24], was closely related to the isolates from two sewage and four human samples (Figure 1a). Murakami et al [36] and Torii et al [25] pointed out that the strains clustered with strain 14-8 were rarely obtained from broilers, other retail poultry, or humans in other regions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Here, all isolates from two each of sewage and human samples, belonging to this serotype, were concurrently identified in June 2019 (Table 3), and their PFGE patterns were indistinguishable from each other (Figure 1c). Moreover, serovar Agona strain 14-8, which was isolated from human and clustered with the isolates from broilers in the Yamanashi Prefecture using whole-genome sequencing [24], was closely related to the isolates from two sewage and four human samples (Figure 1a). Murakami et al [36] and Torii et al [25] pointed out that the strains clustered with strain 14-8 were rarely obtained from broilers, other retail poultry, or humans in other regions.…”
Section: Discussionmentioning
confidence: 98%
“…To estimate the sources of the isolates from sewage, the serovar Agona strain, designated as 14-8, which was isolated from a human in 2014 and clustered with strains isolated from broilers using PFGE analysis and whole-genome sequencing [24,25], was also analyzed. The PFGE pattern of the 14-8 strain was closely related to those of two and four isolates from sewage and humans, respectively, and the antimicrobial resistance pattern was consistent with these six isolates (Figure 1a).…”
Section: Pulsed-field Gel Electrophoresis (Pfge) Analysismentioning
confidence: 99%
“…In addition, in another study, we showed that S . Agona strains isolated from broiler chickens had highly similar genetic profiles, as determined by pulsed field gel electrophoresis (PFGE) analyses and whole genome sequence (WGS) analyses [12]. These results suggested that the serovar shift clone had emerged in the broiler-raising farms, and such a shift could change the incidence of Salmonella infections in humans [12].…”
mentioning
confidence: 99%
“…Two strains isolated from sporadic human cases in Yamanashi prefecture were also investigated (Supplementary Table 1). The molecular epidemiological analysis of the strains in this study was done by PFGE analyses with XbaI or BlnI DNA digests as previously described [12]. Minimum spanning tree (MST) analysis was carried out using the PFGE pattern data obtained in this study and the PFGE data of the serovar shift clone in our previous study [12] using BioNumerics Ver.…”
mentioning
confidence: 99%
See 1 more Smart Citation